The problem of evil: A reading from Leibniz’s theodicy - Kolani, Sougleman (Razón y fe, 2021)
The present essay aims to present the distinction between the types of evil in the thought of the philosopher Gottfried Wilhelm Leibniz (1646-1716). The reflection on evil is present in Theodicy, a kind of science, a doctrine of God’s justice, that is, of both his wisdom and his goodness. Evil is divided into three dimensions: metaphysical, physical, and moral. According to Leibniz, metaphysical evil is the source and origin from which all other evils derive. According to him evil is not an obstacle to God’s goodness. Leibniz argues that God permits evil as a function of the free will.
Keywords: goodness; God; man; freedom; Leibniz; evil